2015
DOI: 10.7314/apjcp.2014.15.23.10067
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Metformin on the Endometrium - a Clinical Trial

Abstract: Background: Unopposed estrogen has a central role in development of endometrial benign, premalignant and malignant lesions. The aim of this study was to evaluate the anti-estrogenic effect of metformin on endometrial histology in comparison with progesterone. Materials and Methods: A total of 43 patients who were referred to our center for abnormal uterine bleeding and had a histologic diagnosis were disordered proliferative endometrium or simple endometrial hyperplasia were included and randomly distributed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 25 publications
1
31
0
2
Order By: Relevance
“…In this study, we reported more responses in both groups compared to the results of other studies (95.1% and 93%). As with the study of Shan et al (11) and Dastranj et al (14), we had no complication in any of the groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, we reported more responses in both groups compared to the results of other studies (95.1% and 93%). As with the study of Shan et al (11) and Dastranj et al (14), we had no complication in any of the groups.…”
Section: Discussionsupporting
confidence: 82%
“…Continuous treatment with megestrol acetate was effective in improving proliferative and hyperplastic disorders of endometrium but its effect on atypical cases was lower (13). Dastranj et al compared the effect of megestrol acetate with metformin and found a higher effect in the metformin group (95.5%) than the megestrol group (63.6%) (14). In comparison to this study, we investigated the comparative effect of combination of megestrol acetate and metformin with megestrol acetate alone on proliferative and hyperplastic endometrial disorders.…”
Section: Discussionmentioning
confidence: 89%
“…In addition two low grade endometrial carcinomas in the metformin group responded very well (Tabrizi et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…However, the majority of these previous studies possessed methodological weaknesses and/or insufficient data. Additionally, experimental studies revealed that metformin is an effective antiestrogenic agent, inhibiting cell proliferation and leading to growth arrest, as well as inducing apoptosis in EC (17,(20)(21)(22). Furthermore, recent findings have suggested that metformin is important in suppressing the migration and invasion of cancer cells, which could prevent metastasis (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%